Thyroid Function in Children with Nephrotic Syndrome and Normal Renal Function in a Tertiary Level Hospital, Rajshahi (TAJ: Journal of Teachers Association, 2019)
Background: Nephrotic syndrome (NS) is a one of most common renal disease in children causing massive proteinuria. In patients with NS, other proteins like thyroid hormones and hormone binding protein are also lost in urine in addition to albuminuria. So, this study was done to find out the thyroid function status of nephrotic syndrome children and to compare the thyroid function of healthy control children.Method: This cross sectional comparative study was carried out in the Department of Paediatrics, Rajshahi Medical College and Nuclear Medicine Centre, Rajshahi. Total 30 patients of both sex and age between 2-12 years diagnosed as nephrotic syndrome were included in this study and another 30 non-nephrotic syndrome apparently healthy children were taken as control. History, clinical examinations and laboratory investigations were recorded in preformed questionnaire. Thyroid function statuses also were evaluated in both patient and healthy control. After data collection, statistical analysis was done by computerized software.Results: In this study, 63.3% (n=19) nephrotic syndrome children had secondary hypothyroidism, overt hypothyroidism was 27.3% (n=7) and subclinical hypothyroidism was 6.7 % (n=2).Conclusion: In patients of childhood nephrotic syndrome different forms of thyroid dysfunctions are commonly associated due to loss of thyroid hormones and hormone binding’s protein.TAJ 2018; 31(1): 62-69